PELATIHAN PEMBELAJARAN AKTIF DALAM PENINGATAN KOMPETENSI GURU MIS AL-AFKARI DELI SERDANG - Banurea, Oda Kinata (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
This active learning strategy is expected to be able to show a picture and motivation for teachers in carrying out learning actively doing or doing each learning process and active learning strategies. This method is included in the relistic active learning approach or student / learner-centered learning. The author also wants to illustrate the mistakes of wrong learning strategies and change the paradigm, that language learning is not only a necessary cognitive factor but involves all learning elements which include cognitive, physical, mental and emotional aspects. In addition, in the realistic mathematics learning process it is not enough to rely on one strategy and one method but using a variety of methods and strategies. Because, each method and strategy has its own advantages.